The significance of placental ratios in pregnancies complicated by small for gestational age, preeclampsia, and gestational diabetes mellitus - Kim, Hee Sun (Korean Society of Obstetrics and Gynecology; Korean Society of Contraception and Reproductive Health; Korean Society of Gynecologic Endocrinology; Korean Society of Gynecologic Endoscopy and Minimal Invasive Surgery; Korean Society of Maternal Fetal Medicine; Korean Society of Ultrasound in Obstetrics and Gynecology; Korean Urogynecologic Society, 2014)
OBJECTIVE: This study aimed to evaluate the placental weight, volume, and density, and investigate the significance of placental ratios in pregnancies complicated by small for gestational age (SGA), preeclampsia (PE), and gestational diabetes mellitus (GDM). METHODS: Two hundred and fifty-four pregnant women were enrolled from August 2005 through July 2013. Participants were divided into four groups: control (n=82), SGA (n=37), PE (n=102), and GDM (n=33). The PE group was classified as PE without intrauterine growth restriction (n=65) and PE with intrauterine growth restriction (n=37). Birth weight, placental weight, placental volume, placental density, and placental ratios including birth weight/placental weight ratio (BPW) and birth weight/placental volume ratio (BPV) were compared between groups. RESULTS: Birth weight, placental weight, and placental volume were lower in the SGA group than in the control group. However, the BPW and BPV did not differ between the two groups. Birth weight, placental weight, placental volume, BPW, and BPV were all significantly lower in the PE group than in the control group. Compared with the control group, birth weight, BPW, and BPV were higher in the GDM group, whereas placental weight and volume did not differ in the two groups. Placental density was not significantly different among the four groups. CONCLUSION: Placental ratios based on placental weight, placental volume, placental density, and birth weight are helpful in understanding the pathophysiology of complicated pregnancies. Moreover, they can be used as predictors of pregnancy complications.